Application of cryopreserved placental polypeptide complex in murine acubarotrauma model - Salnykov, Dmytro; Skoryk, Anastasiya; Shevchenko, Mariia; Shcheniavskyi, Ivan; Chub, Oleg; Voitenko, Stanislav; Osetsky, Oleksandr; Prokopiuk, Olga (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):248